Gamification: How game design and narrative therapy can work together - Luke Kalaf (International Journal of Narrative Therapy and Community Work, 2023)
This paper documents ways of incorporating gamification (using game design elements in a nongame context) into therapeutic conversations using narrative therapy principles to uncover skills and knowledges suppressed by dominant discourses.